Editorial Introduction: Didactic Challenges in the Digital Age - Horváth, László; Fűzi, Beatrix (Pedagógusképzés, 2024)
In an unconventional move, we used artificial intelligence to generate the editorial introduction for this section, putting into practice the topic of one of our articles.